Scaling strategies and mechanisms in small and medium enterprises in the agri-food sector: a systematic literature review - Begimkulov, Emil; Darr, Dietrich (Frontiers in Sustainable Food Systems, 2023)
The question of how small and medium enterprises (SMEs) in the agri-food sector successfully develop and grow their business is a matter of high practical and theoretical relevance. The current paper conducts a systematic literature review focused on two key objectives. First, it explores the conceptual underpinning and evolution of the scaling concept by analyzing relevant conceptual and empirical journal articles. Second, the paper identifies and systematizes the key scaling strategies, drivers and mechanisms implemented by agri-food SMEs by reviewing published business case studies. The study’s findings reveal that agri-food SMEs primarily utilize vertical scaling up, which is achieved through establishing partnership relations, collaboration and integration mechanisms. Horizontal scaling out is another frequently used strategy accomplished via market demand stimulation, product diversification and geographic expansion. In contrast, scaling deep is the least frequently used strategy, which is achieved through transformative learning and cultural mechanisms. Overall, the results contribute to the literature on scaling agri-food SMEs by providing a comprehensive overview and classification of the key strategies, drivers and mechanisms used by agri-food SMEs.